Unlocking Barriers to Adoption and Scaling of Climate Smart Cocoa Practices in Ghana - Dalaa, Mustapha Alasan; Kofituo, Rich Kofi; Amoah, Alvin; Jassogne, Laurence T.P.; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Cocoa production in West Africa has been adversely affected by climate change at varying degrees. The cocoa farming areas in Ghana vary according to severity in impact of climate change and has been delineated into three climatic impact zones namely; Transform, cope and adjust zones. For years, cocoa industry technical experts have recommended Good Agricultural Practices (GAPs) without considering the different farmer typologies across the climate impact zones. The Consultative Group for international Agricultural Research (CGIAR) through the International Institute of Tropical Agriculture (IITA) in Ghana recently documented and aligned climate smart cocoa (CSC) practices across the three impact zones to help farmers mitigate against the effect of Climate change. The aim of this study was to identify farmer typologies in the different climate impact zones and how this affect adoption of CSC recommendations.